Male Domestic Violence - Kane, Tamsin A. (Journal of interpersonal violence, 2000)
This study investigated whether men who use violence toward their partners are more accepting of domestic violence and report higher levels of general aggression and levels of interpersonal dependency than comparison groups (football players and community service volunteers). Participants consisted of 83 men: 23 from an intervention program for violent men, 30 football players, and 30 community service volunteers. Measures of attitudes to the acceptability of domestic violence, aggression levels, and interpersonal dependency levels were administered. Results indicated the violent men were more aggressive and more dependent than both the comparison groups, whereas all three groups had a low tolerance of violence toward female partners. Football players and community service volunteers did not differ in their levels of general aggression. These findings emphasize the importance of intervention programs addressing the areas of male aggression and emotional dependency in their syllabuses as a strategy for curbing male violence toward female partners